Comparison of Business Feasibility, Profits, and Production of Pacific White Shrimp (Litopenaeus Vannamei) Boone Aquaculture Industry, 1931 in Indonesia Ponds - Farkan, Mochammad; Samsuharapan, Sri Budiani; Panjaitan, Amyda Suryati; Nurraditya, Lakonardi; Prabowo, DH Guntur (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Shrimp is a fishery commodity that has high economic value and is an upstream-to-downstream industry. The current problem is the hesitation of farmers and shrimp farming entrepreneurs to develop shrimp farming in ponds. The purpose of this study was to compare the production and financial aspects of Pacific White Shrimp (Litopenaeus vannamei) cultivation in the intensive pond system industry in Indonesia. The data collection method is a field survey. The data analysis method is descriptive and quantitative. Data processing tools used Microsoft Excel and SPSS (Statistical Product and Service Solutions).   The research locations are the shrimp farming industry AM Bangka, SUN Bengkalis, AN Probolinggo, MCS Yogjakarta, and UK Pandeglang. The results showed that the productivity of 18,540-38,498 kg. Ha-1 per cycle, survival rate (SR) 68 -99%, and feed conversion ratio (FCR) 1.05-1.98. Financial analysis R/C ratio 1.04-1.78, and payback period 1 year 28 days - 2 years 9 months. The cost of goods sold per kg of shrimp was US $0.87 to US $3.82.  The prospect of intensive Vaname shrimp farming industry in Indonesia has a good prospect by doing efficiency and effectiveness of production costs.